Pengaruh Brand Ambassador dan Digital Marketing terhadap Purchase Decision pada Produk Wafer Nabati di Jakarta - Listyaningsih Listyaningsih; Budi Kramadibrata (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
The use of brand ambassadors and digital marketing campaigns has become a popular strategy for companies to reach consumers and influence their purchase decisions through social media content, ultimately increasing sales and company profits. This study aims to determine the effect of Brand Ambassador and Digital Marketing on Purchase Decision of Nabati wafer products in Jakarta. The research sample consisted of 96 respondents. A descriptive quantitative method was employed in this study, with the sample selected using simple random sampling. Data analysis techniques included instrument testing, classical assumption testing, multiple linear regression, determination testing, and hypothesis testing. The results showed that Brand Ambassador partially influences Purchase Decision, and Digital Marketing also partially influences Purchase Decision. Additionally, Brand Ambassador and Digital Marketing simultaneously influence Purchase Decision.